Long Non-coding RNA MEG3 Activated by Vitamin D Suppresses Glycolysis in Colorectal Cancer via Promoting c-Myc Degradation - Zuo, Siyu; Wu, Lei; Wang, Yi; Yuan, Xiaoqin (Frontiers in Oncology, 2020)
Colorectal cancer, a common tumor, is characterized by a high mortality rate. Long noncoding RNA maternally expressed gene 3 (MEG3) serves a regulatory role in the carcinogenesis and progression of several types of cancer; however, its role in colorectal cancer remains largely unknown. The aim of this study was to explore the regulatory role and mechanism(s) of MEG3 in colorectal cancer. The “Warburg effect” or “aerobic glycolysis” is characteristic of the metabolism of tumor cells. To determine the effect of MEG3 on glycolysis of colorectal cancer cells, we used an XF analyzer to perform glycolysis stress test assays and found that overexpression of MEG3 significantly inhibits glycolysis, glycolytic capacity, as well as lactate production in colorectal cancer cells, whereas knockdown of MEG3 produced the opposite effect. As to the mechanism, overexpression of MEG3 induces ubiquitin-dependent degradation of c-Myc and inhibits c-Myc target genes involved in the glycolysis pathway such those for lactate dehydrogenase A, pyruvate kinase muscle 2, and hexokinase 2. Moreover, we found that MEG3 can be activated by vitamin D and vitamin D receptor. Clinical data demonstrated that MEG3 is positively associated with serum vitamin D concentrations in patients with colorectal cancer. We found that 1,25(OH)2D3 treatment increases MEG3 expression and vitamin D receptor knockdown abolishes the effect of MEG3 on glycolysis. These results indicate that vitamin D-activated MEG3 suppresses aerobic glycolysis by colorectal cancer cells via degrading c-Myc. Thus, vitamin D may have therapeutic value in the treatment of colorectal cancer.